Ambitious Girl - Harris, Meena; Valdez, Marissa (New York : Little, Brown and Company, 2021)
A girl sees a woman labeled as having too much ambition, but when the girl considers its definition she finds herself inspired and realizes ambition is required to make changes to the world and have her voice be heard.
Keywords: Stories in rhyme; Girls -- Juvenile fiction; Ambition -- Juvenile fiction; Stories in rhyme; Girls -- Fiction; Ambition -- Fiction